Revelation: The Apocalypse of Jesus Christ. By Judith Kovacs and Christopher Rowland. Pp. xviii + 315. (Blackwell Bible Commentaries.) Oxford: Blackwell, 2004. isbn 0 631 23214 1 and 23215 X. Hardback £60/59.95; paper £16.99/24.95 - Boxall, Ian (The journal of theological studies, 2005)
Wirkungsgeschichte, the ‘history of effects’ of biblical texts, is now firmly on the agenda of biblical scholarship within the Academy. This commentary is among the first volumes in the new Blackwell Bible Commentary series, explicitly concerned with Reception History. Of course, there are antecedents, notably Ulrich Luz's fine commentary on the Gospel of Matthew, which combines better-established critical methods with the concerns of Wirkungsgeschichte (and Luz's influence, and behind him that of Gadamer, permeates this book). But Judith Kovacs and Christopher Rowland take us much further. Arguably no biblical book offers richer fare in terms of its reception and influence than the Apocalypse of John, and the authors have offered us rich fare indeed, in this ground-breaking commentary.